Addressing quality and safety in anatomic pathology in low- and middle-income countries - Smith, Stephen M.; Eadara, Amrik; Parkash, Vinita (Frontiers in Medicine, 2022)
The World Health Organization (WHO) has created a sustainable development goal of reducing preventable mortality from cancer in low- and middle-income countries (LMICs) by 30% by 2030. Central to achieving this goal is the creation and maintenance of quality anatomic pathology services (APS). Within the last decade, quality assurance programs and patient safety measures have become a major focus of research for upper middle- and high-income countries (UMHICs), which has led to marked documented improvement in the quality of services provided by laboratories, as well as a decrease in patient safety events. We propose that as APS are developed in LMICs, the lessons learned by UMHICs are necessary to incorporate to produce quality and safe services toward obtaining the aforementioned goal. Furthermore, data suggests that Quality Improvement work requires change at the macrosystems and microsystems levels to achieve these goals. Here, we propose five “microsystems” strategies for professional organizations, healthcare institutions in LMICs and UMHICs that would accelerate quality improvement programs/systems implementation in APS in LMICs.